Exploring the causal impact of body mass index on metabolic biomarkers and cholelithiasis risk: a Mendelian randomization analysis - Feng Zhao; Yanjiang Yang; Wenwen Yang (Scientific Reports)
Abstract Obesity is a well-established risk factor for various diseases, but the mechanisms through which it influences disease development remain unclear. Using Mendelian randomization (MR) analysis, we examined the causal relationship between BMI, 249 metabolic traits, and cholelithiasis. BMI data were obtained from four sources, and cholelithiasis data were from two distinct datasets. We analyzed the direct effect of BMI on cholelithiasis and identified key metabolic mediators. BMI was found to be positively associated with the risk of cholelithiasis across all datasets analyzed. A total of 176 metabolites were identified to be significantly associated with BMI, including amino acids, cholesterol esters, free cholesterol, triglycerides, and phospholipids. Among these, 49 metabolites were identified as mediators in the BMI-cholelithiasis relationship. Specifically, fatty acid levels, cholesteryl esters, phospholipids, triglycerides, and free cholesterol were key mediators in this relationship, with mediation proportions ranging from − 2.38–7.14%. This study provides robust evidence that BMI significantly impacts metabolic biomarkers, which in turn affect the risk of cholelithiasis. These findings highlight the importance of managing BMI to mitigate metabolic dysfunction and reduce the risk of gallstone formation. Future research should explore the specific metabolic pathways involved to identify potential therapeutic targets.